Radiation shield of therapeutic electron accelerator “CLINAC” - Voronko, V.A.; Dovbnya, A.N.; Pugachev, G.D.; Sotnikov, V.V.; Uvarov, V.L.; Shestakova, V.S. (Вопросы атомной науки и техники, 2017)
It is anticipated that a therapeutic electron accelerator “Clinac” (manufactured by Varian Co., USA) will be installed at NSC KIPT. It has been suggested that the available compartment having thick concrete walls might be used as a medical treatment room. In this connection, the analysis has been made for correspondence of the com-partment protection characteristics to the accelerator safe operation requirements. The protection capability was estimated for a mode of the accelerator operation at electron energy of 18 MeV with a target made of tungsten. Equivalent dose rates behind the shield were calculated with due regard for the direct bremsstrahlung from the target, and also, for the scattered photon emission and neutron radiation. To reduce the scattered radiation level in the entrance area, the variant of shielding maze has been proposed. The estimated radiation dose of the accelerator staff does not exceed the values permissible by the radiation safety standards. According to the calculations made, the concentration of ozone produced in the treatment room will be also below the MPC level.